Cooperative Localization Bounds for Indoor Ultra-Wideband Wireless Sensor Networks. (23rd December 2007) - Alsindi Alsindi, Nayef Nayef; Pahlavan Pahlavan, Kaveh Kaveh
Abstract : In recent years there has been growing interest in ad-hoc and wireless sensor networks (WSNs) for a variety of indoor applications. Localization information in these networks is an enabling technology and in some applications it is the main sought after parameter. The cooperative localization performance of WSNs is constrained by the behavior of the utilized ranging technology in dense cluttered indoor environments. Recently, ultra-wideband (UWB) Time-of-Arrival (TOA) based ranging has exhibited potential due to its large bandwidth and high time resolution. The performance of its ranging and cooperative localization capabilities in dense indoor multipath environments, however, needs to be further investigated. Of main concern is the high probability of non-line of sight (NLOS) and Direct Path (DP) blockage between sensor nodes which biases the TOA estimation and degrades the localization performance. In this paper, based on empirical models of UWB TOA-based Outdoor-to-Indoor (OTI) and Indoor-to-Indoor (ITI) ranging, we derive and analyze cooperative localization bounds for WSNs in different indoor multipath environments: residential, manufacturing floor, old office and modern office buildings. First, we highlight the need for cooperative localization in indoor applications. Then we provide comprehensive analysis of the factors affecting localization accuracy such as network and ranging model parameters.